Guide for analyzing the quality of virtual learning objects in Colombian basic and middle education - Molano-Puentes, Fredy Ulises; Alarcón-Aldana, Andrea Catherine; Callejas-Cuervo, Mauro (Universidad Pedagógica y Tecnológica de Colombia, 2018)
A guide to evaluation of the quality of Virtual Learning Objects (VLO) is presented as support for basic secondary and middle education. The pedagogical aspects and curriculum guidelines issued by the Ministry of National Education (MEN, Spanish acronym) for areas of knowledge taught in Colombian institutions are taken as a reference. The study was carried out using an instrument design with a quantity scale factor, based on a hermeneutic analysis of the pedagogical guidance documents and the standards and curriculum guidelines established by the MEN. In order to formulate the evaluation instrument, constructivism was considered. This guide is supported by factors of critical meaningful learning and by aesthetic, technological, and content elements. Its compatibility is given by learning objects evaluation methodologies such as LORI, COdA and ECOBA. As a result, a guide to evaluation of the quality of VLO was designed and validated, which includes a metric formulated for carrying out a statistical study of reasoning. Its main objective is to verify the implementation of guidelines and basic learning rights in the Colombian education context.